"Like a ball and chain": Altering locomotion effort perception distorts spatial representations. (December 2018) - Lhuillier, Simon; Gyselinck, Valérie; Dutriaux, Léo; Grison, Elise; Nicolas, Serge
Abstract: This study aimed at demonstrating the role of sensorimotor information through the influence of walking effort perception on the process of route planning for navigation. Participants were asked to walk wearing weighted or non-weighted ankle belts prior to learning virtual environments. They then had to plan routes between landmarks and to estimate travel times and distances for each route. Results newly showed that loaded ankle weights made participants underestimate their own self-reported walking speed compared to the non-loaded participants. In addition, participants with low spatial ability tended to spend more time planning their route when wearing weighted belts than with non-loaded belts. Loaded ankle weights also negatively affected performances on a spatial memory task: landmark position retrieval on a map. These results provide support for embodied views of spatial cognition. Highlights: Experiencing increased locomotion effort distorts walking speed perception but not actual walking speed. Participants with low spatial ability tend to spend more time planning routes when wearing ankle weights. Wearing ankle weights alters spatial memory retrieval. Motor simulation and anticipated physical effort could play a role in spatial processing.